Feral Experiments in CreaTures Co-Laboratory - Dolejšová, Markéta; Botero, Andrea; Hee-jeong Choi, Jaz; Mitro, Michal; Pokrywka, Agniezska; Mattelmäki, Tuuli; Chewie, Škubánek (Research in Arts and Education, 2024)
We share insights from our practice-based experimentation with ‘feral’ ways of sensemaking in the context of creative transformational practices. Drawing on three art and design research projects, we discuss how feral ways–open-ended, spontaneous, welcoming indeterminacy – may foster more-than-human co-creation of knowledge and data, and nurture shifts from anthropocentric ‘making sense of’ to relational ‘making sense-with’ other-than-human creatures. Through our cases, we illustrate how experimenting with feralness can foreground issues of power, agency, and control in the currently human-centric discourses around data, technology, and sensemaking in eco-social transformation. Our insights may nurture critical more-than-human perspectives in creative eco-social inquiries.